The research journal TRANSPORT: peer-reviewing process in 2016 - Prentkovskis, Olegas; Junevičius, Raimundas (Transport, 2016)
"The research journal TRANSPORT: peer-reviewing process in 2016" Transport, 31(4),  p. 450-460